The incidence and risk factors of hypocalcaemia after thyroid surgery - Abed, Aws B.; Al Bermani, Mohannad K.; Salman, Waleed A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Hypocalcaemia is a well-recognized complication of thyroid surgery. It is the most often transient event that occurs after extensive thyroid resection that may require calcium and/or vitamin D supplements to alleviate or prevent the symptoms.Objective: of this study is to determine the incidence of hypocalcaemia after thyroid surgery and find out the risk factors involved regarding the patient age, gender, and muscular build, clinical diagnosis, the extent of surgery, ligation of the inferior thyroid artery, pathology report and the experience of the surgeon.Patients and methods: This prospective study was carried out on 100 patients who underwent thyroid surgery for various thyroid diseases at the surgical department of Baghdad teaching hospital in the period between November 2009 to November 2013.Serial serum calcium measurements were recorded as well as details of the operation, patient age and gender, ligation of the inferior thyroid artery or not, pathological report and experience of the operator. Hypocalcaemia was considered transient if it was resolved within 6 months and permanent if it persisted after 6 months and the patient was maintained on supplementation therapy of calcium and vitamin D.Results: We found that the incidence of post-thyroidectomy hypocalcaemia was 30 % and in the majority of the cases (24%) was transient, while it was permanent in only (6%) of cases and had occurred mainly after total thyroidectomy and in cases with ligation of the inferior thyroid artery.Conclusions: We concluded that post thyroidectomy hypocalcaemia is a relatively common complication, but it is transient in the majority of the patients. Its incidence is related to the extent of the surgery and can be reduced by the use of the correct surgical procedures.Keywords: hypocalcaemia, post thyroidectomy, total thyroidectomy, subtotal thyroidectomy